ANALISIS PENGARUH MOTIVASI KERJA, KOMITMEN ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PERUSAHAAN ROKOK PT MAJU ABADI SIGARET DI KUDUS - Andy Wijaya Eka Saputra, 0835020558; Waruwu, Penunjang (Students Journal of Economic and Management, 2012)
This study is a test Effect Analysis Work motivation, organizational commitment and work environment of the Company Employee Job Satisfaction Cigarette smoking PT.Maju Eternal Spirit. The population in this study were employees of tobacco companies PT.Maju Eternal Spirit Cigarettes totaling 80 people, then the results of the research data was tested with the validity and reliability, the result, the whole construct produce valid and reliable values. Further analysis researchers used multiple regression analysis to explain the relationship between these variables. The result is work motivation, organizational commitment, and work environment positive and significant effect on job satisfaction. It can be concluded that if the level of motivation, organizational commitment, and work environment, the better it will produce job satisfaction is also high. This is consistent with the review of existing theories and the results of an analysis of previous studies. It is expected that the leadership and pegawaiperusahaan order to maintain the level of motivation, commitment, and work environments that improve employeesatisfaction, which in turn organizational goals can be achieved together.